(untitled) (Research, Society and Development, 2022)
The pandemic caused by the SARS-CoV-2 virus began in December 2019 and was one of the biggest public health crises in recent years. It is known that the spread of the disease not only harmed infected patients, but also indirectly affected millions of other individuals around the world. The consequence of the precariousness in the care of pregnant and postpartum women, for example, resulted in numerous organic and psychological complications. By intensifying stressors and imposing distance between the parturient and her support network, the pandemic made the pregnancy-puerperal cycle an even more complex and lonely moment, thus causing a drastic increase in the rates of gestational and postpartum depression. Despite the importance of this involvement, the number of studies dedicated to understanding this causal relationship remains scarce, given that the chaotic situation caused by the virus has recently started to improve. Therefore, this research aimed to demonstrate the deleterious impact of COVID-19 on the mental health of pregnant and parturient women. Therefore, a systematic literature review was carried out, with a descriptive and qualitative character, based on the analysis of nineteen scientific articles available in the various health databases. The detailed study of the bibliography made it possible to conclude the irrefutable maleficence of the pandemic in the pregnancy-puerperal cycle, for which the expansion of mental health care is recommended, both in public and private services. Furthermore, it is essential to carry out more studies in the area, to solidify the scientific findings and conclusions, contributing to improve the general well-being of these patients.